2024
DOI: 10.1002/1873-3468.14857
|View full text |Cite
|
Sign up to set email alerts
|

Comparative structural and functional analysis of the glycine‐rich regions of Class A and B J‐domain protein cochaperones of Hsp70

Szymon J. Ciesielski,
Brenda A. Schilke,
Milena Stolarska
et al.

Abstract: J‐domain proteins are critical Hsp70 co‐chaperones. A and B types have a poorly understood glycine‐rich region (Grich) adjacent to their N‐terminal J‐domain (Jdom). We analyzed the ability of Jdom/Grich segments of yeast Class B Sis1 and a suppressor variant of Class A, Ydj1, to rescue the inviability of sis1‐∆. In each, we identified a cluster of Grich residues required for rescue. Both contain conserved hydrophobic and acidic residues and are predicted to form helices. While, as expected, the Sis1 segment do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 40 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…(C) AlphaFold predictions for Sis1-121 (left) and Ydj1-101 (right). In Sis1-121, Helix V interacts with Helices II and III and sterically blocks the HPD motif; this location for Helix V is congruent with NMR data for Sis1 ( Ciesielski, et al, 2024 ) and similar to that observed in NMR structures of the human Sis1 ortholog DNAJB1 ( Faust et al, 2020 ). In Ydj1-101, Helix V is in the foreground on the right side, away from Helix II and III and the HPD motif.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…(C) AlphaFold predictions for Sis1-121 (left) and Ydj1-101 (right). In Sis1-121, Helix V interacts with Helices II and III and sterically blocks the HPD motif; this location for Helix V is congruent with NMR data for Sis1 ( Ciesielski, et al, 2024 ) and similar to that observed in NMR structures of the human Sis1 ortholog DNAJB1 ( Faust et al, 2020 ). In Ydj1-101, Helix V is in the foreground on the right side, away from Helix II and III and the HPD motif.…”
Section: Discussionsupporting
confidence: 83%
“…Sis1 has DAFNIFSQFF, containing residues important for prion maintenance and the ability of Sis1-121 to rescue the lethality of sis1 -∆ ( Lopez et al, 2003 ). Residues in this region form a helix in Ydj1, Sis1, and its human ortholog, DNAJB1, referred to as “Helix V” in the literature as it is typically the predominant helix after the four helices of the J-domain ( Ciesielski, et al, 2024 ). The remaining 40 residues comprise another low complexity region highly enriched in S, N, and F residues (38% S, 18% N, 13% F, and 8% G).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations